FAKTOR YANG MEMPENGARUHI PREFERENSI PEMUKIMAN DALAM MENENTUKAN LOKASI PERUMAHAN DI PERUMAHAN BUKIT SUKOREJO DAN PERUMAHAN TRANGKIL SEJAHTERA KECAMATAN GUNUNGPATI - Raharjo, Sudono Salim; Sriyono, Sriyono (Geo-Image, 2017)
This study aims to identify factors that affect consumers for choosing Bukit Sukorejo Residence and Trangkil Sejahtera Residence as their settlement. The approach used in this study is quantitative correlation with looking for a relationship or correlation between variables. The focus in this research is preference residence for determining the location of house in Bukit Sukorejo Residence and Trangkil Sejahtera Residence. This research selects a cross-table analysis as the data analysis techniques. The results obtained are level of education, financial status, aesthetic location, prestige location, accessibility to employment and service facilities, and the environment values.